MAKNA RELIEF TAPAL KUDA PADA CANDI SUKUH DALAM PERSPEKTIF PENDIDIKAN AGAMA HINDU - Putu Budiadnya (Widya Aksara, 2020)
The temple has become a monument to the civilization and pride of the Indonesian people. The pride of this monumental historical building has been proven by the government's program to renovate and reconstruct and maintain and preserve temples as historical relics throughout the country so that it becomes a historical tourism area. Sukuh Temple is found in Karangayan Regency. In this temple there are different relifs from other temples in the Middle Ages. Relif Horseshoe in Sukuh Temple is a philosophy of paraning dumadi. The Horseshoe Relif is located within the surroundings of Sukuh Temple which is a cultural preservation of historical, scientific, national and state development. Sukuh Temple has noble values ??that must be preserved in order to strengthen the practice of increasing national dharma, strengthening national unity, and improving the welfare of society. Based on this background, the research problem can be formulated as follows: What is the shape of the Horseshoe Relif at Sukuh Temple? What is the meaning of Relief Horseshoe Hindu Religious Education Perspective? Sangkan Paraning Dumadi in the Kejawen philosophy teaches that the ultimate goal of human life is God Almighty, so that in living this life we ??must approach the noble values ??of God. Honest, Fair, Responsibility, Caring, Simple. In the teachings of Hindu hospitality there is a way to reach perfection, namely Moksa, by connecting and focusing one's mind to Ida Sang Hyang Widhi Wasa called Catur Marga Yoga, Ast?ngga yoga, namely yama, nyama, asana, pranayama, pratyahara, dharana, dhyana and samadhi and samadhi The Ethics Education Values ??contained in the Javanese dance are very paraning. Dumadi The noble values ??of the divinity include honesty, fairness, responsibility, caring, simple, friendly, disciplined and this commitment can be found in the tembang dangganggula heritage of the ancestors who until this moment. still being echoed. The value of ethical education contained in the Horseshoe Relif is very relevant to the needs of ethical education standards for Hindus in particular, and humanity in general. Dhana or not greedy nature is very relevant to the guidelines of human morality at this time, especially to avoid the occurrence of global warming which is more due to the nature of human greed in exploiting natural resources on this earth.